Rozkład naprężeni stycznych wzdłuż sztywnego pręta znajdującego się wewnątrz półpłaszczyzny sprężystej - Bauer, J.; Strzelecki, T. (Engineering Transactions, 1969)
The subject of the present considerations is a semi-infinite elastic plate loaded indirectly, by means of a thin rigid bar inside this plate. Our aim is to determine the distribution of the shear stress over the lateral surface of the bar, which is loaded by a concentrated force. The problem is solved making use of the solutions for concentrated forces by reducing the boundary conditions to weakly singular Fredholm integral equations of the first kind. This equation is solved numerically and the results are represented in Fig. 5.